Whole-genome microRNA sequencing analysis in patients with pulmonary hypertension - Chen, Shi; Zhong, Jinnan; Hu, Bingzhu; Shao, Nan; Deng, Chaosheng (Frontiers in Genetics, 2023)
Pulmonary hypertension (PH) is a pathological disorder with multiple clinical manifestations that lead to cardiovascular and respiratory diseases in most patients.Recent studies have revealed that microRNAs (miRNAs) play important roles as upstream signaling molecules in several diseases, including PH. However, miRNAs that can be used as diagnostic or prognostic biomarkers for PH have not been identified.Thus, in this study, peripheral blood samples obtained from patients with PH and healthy individuals were subjected to genome-wide miRNA sequencing and transcriptome analysis. We screened 136 differentially expressed miRNAs in patients with PH and verified that four differentially expressed miRNAs, namely, hsa-miR-1304-3p, hsa-miR-490-3p, hsa-miR-11400, and hsa-miR-31-5p, could be used as clinical diagnostic biomarkers for pulmonary arterial hypertension. Our findings provide a basis for further in-depth investigations of the specific mechanisms of miRNAs in PH.